Which is the Best Alternative for Displaced Femoral Neck Fractures in the Elderly?: A Meta-Analysis - Gao, Hongwei; Liu, Zhonghao; Xing, Deguo; Gong, Mingzhi (Clinical orthopaedics and related research, 2012)
Background Treatment of displaced femoral neck fractures includes internal fixation and arthroplasty. However, whether arthroplasty or internal fixation is the primary treatment for displaced femoral neck fractures in elderly patients remains a subject for debate. The literature contains conflicting evidence regarding rates of mortality, revision surgery, major postoperative complications, and function in elderly patients with displaced femoral neck fractures treated either by internal fixation or arthroplasty (either hemiarthroplasty or THA). Questions/purpose We determined mortality, revision surgery rates, major surgical complications (which include infection, nonunion or early redisplacement, avascular necrosis, dislocation, loosening of the prosthesis, acetabular erosion, fracture below or around the implant, and other severe general complications such as deep vein thrombosis and pulmonary embolism), and function in patients treated with either internal fixation or arthroplasty for displaced femoral neck fractures in the elderly. Methods We searched PubMed, Embase, and the Cochrane Library for randomized controlled trials (RCTs) comparing internal fixation and arthroplasty. We identified 20 RCTs with 4508 patients meeting all the criteria for eligibility. We performed a meta-analysis of the major complications, reoperations, function, pain, and mortality. Results Compared with internal fixation, arthroplasty reduced the risk of the major complications (95% CI, 0.21–0.54 for 1 year; 95% CI, 0.16–0.31 for 5 years) and the incidence of reoperation 1 to 5 years after surgery (95% CI, 0.15–0.34 for 1 year; 95% CI, 0.08–0.24 for 5 years), and provided better pain relief (95% CI, 0.34–0.72). Function was superior (RR = 0.59; 95% CI, 0.44–0.79) for patients treated with arthroplasty than for patients treated by internal fixation. However, mortality 1 to 3 years after surgery was similar (95% CI, 0.96–1.23, p = 0.20 for 1 year; 95% CI, 0.91–1.17, p = 0.63 for 3 years). Conclusions Arthroplasty can reduce the risk of major complications and the incidence of reoperation compared with internal fixation, and provide better pain relief and function, but it does not reduce mortality. Level of Evidence Level II, prognostic study. See the Guidelines for Authors for a complete description of levels of evidence.